2012
DOI: 10.2174/1874467211205010036
|View full text |Cite
|
Sign up to set email alerts
|

APE1/Ref-1Role in Redox Signaling: Translational Applications of Targeting the Redox Function of the DNA Repair/Redox Protein APE1/Ref-1

Abstract: The heterogeneity of most cancers diminishes the treatment effectiveness of many cancer-killing regimens. Thus, treatments that hold the most promise are ones that block multiple signaling pathways essential to cancer survival. One of the most promising proteins in that regard is APE1, whose reduction-oxidation activity influences multiple cancer survival mechanisms, including growth, proliferation, metastasis, angiogenesis, and stress responses. With the continued research using APE1 redox specific inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
183
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(190 citation statements)
references
References 157 publications
2
183
0
5
Order By: Relevance
“…Ape1 also possesses a redox domain, which allows it to alter transcription factor DNA binding and therefore gene expression. Through its redox function, Ape1 has been shown to regulate the p53, AP-1, and HIF-1a transcription factors, and expression of their downstream target genes implicated in homologous recombination repair, mismatch repair, and global genome repair (43). Accordingly, Ape1-knockout mice die early in embryonic development (44), whereas heterozygous Ape1 mice experience increased spontaneous mutagenesis (45).…”
Section: Waf1mentioning
confidence: 99%
See 1 more Smart Citation
“…Ape1 also possesses a redox domain, which allows it to alter transcription factor DNA binding and therefore gene expression. Through its redox function, Ape1 has been shown to regulate the p53, AP-1, and HIF-1a transcription factors, and expression of their downstream target genes implicated in homologous recombination repair, mismatch repair, and global genome repair (43). Accordingly, Ape1-knockout mice die early in embryonic development (44), whereas heterozygous Ape1 mice experience increased spontaneous mutagenesis (45).…”
Section: Waf1mentioning
confidence: 99%
“…This suggests that Ape1 downregulation may be integral to the enhanced DNA damage observed in LAFP-expressing cells treated with vorinostat. Generally, Ape1 overexpression has been correlated with aggressive proliferation and poor prognosis (43,46,47). Decreasing Ape1 levels via knockdown or chemical inhibition has been shown to reduce cancer cell growth and sensitize cells to DNA-damaging agents (48,49).…”
Section: Waf1mentioning
confidence: 99%
“…Apurinic/apyrimidinic endonuclease 1/redox factor‐1 (APE1/Ref‐1; henceforth referred to as APE1) is a multifunctional protein that is involved in repairing DNA damage via its endonuclease activity in base excision repair (Fung and Demple, 2005; Izumi et al ., 2005; Jiang et al ., 2009; Kelley et al ., 2014), and using its redox protein–protein signaling function to control the activity of numerous transcription factors such as STAT3, NFκB, AP‐1, p53, and hypoxia‐inducible factor 1α (HIF1α), among others (Cardoso et al ., 2012; Fishel et al ., 2015; Gaiddon et al ., 1999; Jiang et al ., 2010; Kelley et al ., 2012; Lando et al ., 2000; Logsdon et al ., 2016). It also contributes to the removal of damaged bases within RNA (Poletto et al ., 2016; Vascotto et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While a number of studies have investigated genes regulated by APE1, and specifically its redox signaling function (Cardoso et al ., 2012; Fishel et al ., 2015; Gaiddon et al ., 1999; Jiang et al ., 2010; Kelley et al ., 2012; Lando et al ., 2000; Logsdon et al ., 2016; Nishi et al ., 2002; Xanthoudakis et al ., 1992), it has been difficult to compile a comprehensive list of genes regulated by APE1 as it is essential for cell viability. APE1‐knockout in mice results in embryonic lethality, postimplantation, between days E5‐E9 (Ludwig et al ., 1998; Xanthoudakis et al ., 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, it is possible that Trx1 may exert a protective role against DNA damage through inhibiting translation by regulating phosphorylation of 4E-BP1 to save energy, possibly through cell cycle arrest by affecting p21 stability and allowing more time for DNA repair, thus eventually reducing MMS-induced cell death and enhancing cell survival. Indeed, protection of Trx1 against MMS-induced DNA damage could have been involved in DNA repair as redox signalling has been shown to affect APE1/Ref1 function, an apurinic/apyrimidinic endonuclease in the DNA base excision repair pathway (38,39), and APE1/Ref1 was shown to regulate the p53/p21 system (37,40). In addition, it was reported that the heat-stable cytosolic factor that promotes glucocorticoid receptor binding to DNA after MMS treatment is neither thioredoxin nor ribonuclease (41), suggesting that Trx1-mediated protection against MMS-induced DNA damage might be specific through certain cellular factors.…”
Section: Resultsmentioning
confidence: 99%